Improving the Diagnosis and Treatment of Early Gastric Cancer in the West - Libânio,Diogo (2022)
Abstract Gastric cancer is the third leading cause of cancer-related death. In Western countries, its lower prevalence and the absence of mass screening programmes contribute to late diagnosis and a slower implementation of minimally invasive treatments. A secondary prevention strategy through endoscopic surveillance of patients at high risk of intestinal-type gastric adenocarcinoma or by screening gastric cancer within colorectal screening programmes is cost-effective in intermediate-risk countries, though the identification of these patients remains challenging. Virtual chromoendoscopy with narrow-band imaging improves the accuracy of endoscopic diagnosis, significantly increasing the sensitivity for intestinal metaplasia while preserving specificity. Endoscopic grading of gastric intestinal metaplasia is feasible, correlates well with histological staging systems and also with gastric neoplasia risk and can be used to stratify risk. Endoscopic submucosal dissection (ESD) in the West achieves efficacy and safety outcomes similar to those reported for Eastern countries, and the long-term disease-specific survival is higher than 95%. A prospective comparative study with gastrectomy confirms its higher safety and its benefits concerning health-related quality of life. However, ESD is associated with a 5% risk of postprocedural bleeding and a 20% risk of non-curative resection. The knowledge of risk factors for adverse events and non-curative resection can improve patient selection. The risk of metachronous lesions after ESD is high (3-5% per year), and endoscopic surveillance is needed. The management of patients with non-curative resection can be optimized using risk scoring systems for lymph node metastasis.